Combined Effects of Induced Water Deficit and Foliar Application of Silicon on the Gas Exchange of Tomatoes for Processing - Morato de Moraes, Diogo Henrique; Mesquita, Marcio; Magalhaes Bueno, Amanda; Alves Flores, Rilner; Elias de Oliveira, Henrique Fonseca; Raimundo de Lima, Frederico Simoes; Mello Prado, Renato de [UNESP]; Battisti, Rafael (Mdpi, 2020)
The beneficial effects of silicon (Si) on plants have been widely reported for its fruit qualitative improvements, growth gains, and protection against abiotic and biotic stresses. This study aimed to evaluate the combined effect of soil water potential (psi s) (-30 and -60 kPa) and the foliar application of Si (0.0 (control), 1.0, 2.0, 3.0, and 4.0 g L-1) in the development of tomatoes grown in a greenhouse. We evaluated the biometric parameters and gas exchange in three periods (20, 34, and 48 days after planting). The rates of transpiration (E), stomatal conductance (gs), and net photosynthesis assimilation (A(n)) were lower when the plants were subjected to water deficit. The foliar application of Si attenuated the effect of the water deficit in both levels applied to the crop. A high response was observed at -60 kPa, regardless of the evaluated period. However, a significant effect was not observed on the relative chlorophyll index and biomass accumulation when Si was applied. A foliar application up to 2.8 g L-1 promotes increases in A(n), gs, and E. It is highlighted that Si can promote improvements in gas exchange when plants are affected by a water deficit.
Keywords: Solanum lycopersicum L; growth; silicon application method; water-plant relationship